Pengaruh Konflik Peran Ganda Dan Stres Kerja Terhadap Kinerja Polisi Wanita Di Polresta Surakarta - Sari, Ririn Wedya Putri Mayang (2016)
Conflict the dual role can faced by some women career who work among them was as policewoman. Policewoman has a duty and responsibilities equal to the police man , it is been described in undang-undang no. 2 years police 2002 about the indonesian government . Policewoman must be to obey regulation which is in police, one about working hours, anywhere policewoman was and when got a call from the commander of then must be implemented irrespective of time and place. The family who feel uncomfortable for be mostly the time it is in office , sometimes demanded to spend time with family . This is one of a trigger the onset of the stress that it would affect on a polwan performance. This study attempts to analyze the influence of conflict the dual role and job stress on performance policewoman in polresta surakarta. Included in this study used technique purposive with the convenience of sampling amounting to 63 respondents. Independent variable this study the conflict the dual role and job stress , while dependent variable policewoman the performance. Analysis of data used covering the validity, the realibilitas, regression analysis multiple, the ( r2 ) determination, test t and the f. The result showed that simultaneously conflict the dual role and job stress significant on performance policewoman. A partial shows that conflict the dual role no significant on performance policewoman .While job stress it has some positive effects significantly to performance policewoman . Therefore, to improve their performance woman policeman job stress need to managed as optimal as possible before by giving workload appropriate. Keywords: Dual Role Conflict, Work Stress and Employee Performance.